Multifunctional cellulose membranes with antibacterial activity and infrared insulation properties for personal thermal management application. Issue 3 (11th February 2022) - Chen, Mingliang; Shan, Zhaoyu; Bin, Gu; Qiu, Fengxian; Wang, Zhuoqun; Zhang, Tao
ABSTRACT: In this work, multifunctional cellulose membranes (Ag-NWs/CMs@Ag) with antibacterial activities, high air permeability, and infrared preservation properties were successfully prepared for personal thermal management application. Infrared radiation preservation was observed by modifying surface's physical and chemical properties. Additionally, Ag-NWs/CMs@Ag exhibits high air permeability of 3.00 mg/cm 2 ·hour, the excellent antibacterial activity against E. coli and S. aureus and hydrophobic properties with a stable water contact angle of 129.35°. Overall, the results of this study demonstrate Ag-NWs/CMs@Ag offers great potential in personal thermal management application and provide an effective strategy for the development of wearable textiles.